(untitled) (Journal of Libya for geographical studies, 2023)
This study seekd to analyze the locations of private pharmacies in the municipal branch of Shuhada’a al- Rumaila, as well as to show their spatial distribution using geographical information systems technology, the study adopted the analytical method in order to analyze the data of pharmacies using spatial statistics method provided in ArcGIS 10.5 software, in addition to use the cartographic representation technique. The study concluded that there is a spatial variation in terms of the numeric distribution of pharmacies in the study area, also the number of existing pharmacies exceeded the number of assumed pharmacies, and this indicates that the planning criteria are not followed when issuing licenses to establish a new pharmacies.